2010
DOI: 10.1038/cr.2010.181
|View full text |Cite
|
Sign up to set email alerts
|

The endoplasmic reticulum-associated degradation is necessary for plant salt tolerance

Abstract: Eukaryotic organisms have quality-control mechanisms that allow misfolded or unassembled proteins to be retained in the endoplasmic reticulum (ER) and subsequently degraded by ER-associated degradation (ERAD). The ERAD pathway is well studied in yeast and mammals; however, the biological functions of plant ERAD have not been reported. Through molecular and cellular biological approaches, we found that ERAD is necessary for plants to overcome salt stress. Upon salt treatment ubiquitinated proteins increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
155
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(159 citation statements)
references
References 52 publications
(75 reference statements)
4
155
0
Order By: Relevance
“…These altered proteins induce endoplasmic reticulum stress that triggers their degradation by the 26S proteasome (Liu et al, 2011). Recently, it has been shown that endoplasmic reticulum-associated degradation of proteins is critical for plant salt tolerance (Liu et al, 2011;Cui et al, 2012) and that protein modification by ubiquitination is essential for disordered/unfolded protein degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These altered proteins induce endoplasmic reticulum stress that triggers their degradation by the 26S proteasome (Liu et al, 2011). Recently, it has been shown that endoplasmic reticulum-associated degradation of proteins is critical for plant salt tolerance (Liu et al, 2011;Cui et al, 2012) and that protein modification by ubiquitination is essential for disordered/unfolded protein degradation.…”
Section: Introductionmentioning
confidence: 99%
“…These altered proteins induce endoplasmic reticulum stress that triggers their degradation by the 26S proteasome (Liu et al, 2011). Recently, it has been shown that endoplasmic reticulum-associated degradation of proteins is critical for plant salt tolerance (Liu et al, 2011;Cui et al, 2012) and that protein modification by ubiquitination is essential for disordered/unfolded protein degradation. Ubiquitin (Ub), a small peptide of 76 amino acids, is transferred to specific substrates through a cascade of reactions mediated by E1 (Ubactivating enzyme), E2 (Ub-conjugating enzyme), and E3 (Ub ligase) (Hochstrasser, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that an Arabidopsis mutant defective in both IRE1A and IRE1B genes grown under high temperature contains less viable pollen grains, indicating the importance of the UPR in pollen development under high temperature (Deng et al 2016). However, whether the UPR plays important roles in salt stress tolerance has not been investigated, although there has been some reports showing the connection between salt stress tolerance and ER-associated degradation, which is part of ERQC machineries induced during the UPR (Cui et al 2012;Liu et al 2011).…”
mentioning
confidence: 99%
“…In the present study, we investigated whether mutants deficient in IRE1 genes show enhanced salt stress sensitivity since the ERQC has been implicated in salt stress responses in plant (Cui et al 2012;Liu et al 2011). In our growth condition, ire1a-2 ire1b-1 mutant seedlings showed shorter roots, consistent with the previous report .…”
mentioning
confidence: 99%
“…1,3,4 Salt stress induces unfolded protein response (UPR) in plants. 5,6 Then, excessively accumulated unfolded proteins may cause ER stress. 7 Many previous studies have demonstrated that ER stress and UPR are involved in plant responses to environmental stresses.…”
mentioning
confidence: 99%